PENGARUH KUALITAS PELAYANAN, KELENGKAPAN PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Mutia, Agustina; Rahma, Sri; Gustina, Chairunnisa (Institut Agama Islam Negeri Kerinci, 2024)
Purpose: This research aims to determine and analyze the influence of service quality, product completeness, and location on purchasing decisions. Design/Methodology/Approach: The method used is a quantitative method with data analysis, namely the Determinant Coefficient Test. Findings: The research results show that service quality, product completeness, and location have a positive and significant effect on purchasing decisions. Research Implications: The results of calculating the coefficient of determination show that the variables of service quality, product completeness and location are 39% and the remaining 61% are influenced by other variables outside this research.